MANAGEMENT OF INFECTED WOUND WITH KSHARAPLOTA DRESSING - A CASE STUDY - Anantkumar V. Shekokar*; Vijay P.Ukhalkar (AYUSHDHARA, 2018)
Acharya Sushruta the pioneer of Indian surgery described various surgical diseases and its management in detail. In which Vrana is utmost important. Acharya Sushruta in his text widely classified the word Vrana with its etiology, site, stage, odour and given various rescue modules for its management. Each and every type of wound requires systemic and local care for healthy and early healing. Cleaning and bandaging is important local procedure to expel out unhealthy, vitiated tissue, debris, dead cells and pus and for the generation of newer healthy tissue mass. The management of lower extremity wound is a difficult task. It is necessary that clinician involved in wound care address both the systemic and local precipitating factors. Dushta Vrana defines as the Vrana vitiated by aggravation of Dosha. Dushta Vrana or infected wound has typical character like foul smell, unusual color with abundant discharge, severe pain and greater healing time. Acharya Sushruta has mentioned various dressing materials for wound healing and it includes Pichu, Plota, Kawalika, etc. In these Plota is better because of its dual purpose i.e. wound toileting as well as to cover the wound. Usually patient avoids surgical debridement due to pain, fear and psychological factors. Therefore there is scope for non-surgical debridement modalities which are also known as parasurgical methods. The Aim of this study is to demonstrate that how a Ksharaplota dressing is used to treat an infected wound which was slow healing or can say fails to heal. At the end we have got the desired and satisfactory results of Ksharaplota dressing which will definitely encourage us for new research with Ksharaplota in near future.